Factors Associated with Not Drinking Alcoholic Beverages in Dependent Individuals on Recovery - Linda Azucena Rodríguez Puente (Universidad de Antioquia, 2018)
Objective This work sought to determine the association between personal factors and not drinking alcoholic beverages in alcohol-dependent individuals on recovery process.